Personal identity - Perry, John (Berkeley : University of California Press, 2008)
This book brings together the contributions of various philosophers to the topic of personal identity. It includes essays that span from John Locke's seventeenth-century attempt to define personal identity through memory, to twentieth-century defenses and critiques of the Lockean view by Anthony Quinton, Sydney Shoemaker, and David Hume.
Includes bibliographical references.
Keywords: Conscience; Consciousness; Personality; Self (Philosophy).